COVID-19: Research Directions for Non-Clinical Aerosol-Generating Facilities in the Built Environment - Roger C. K. Law; Joseph H. K. Lai; David John Edwards; Huiying (Cynthia) Hou (Buildings, 2021)
Physical contact and respiratory droplet transmission have been widely regarded as the main routes of COVID-19 infection. However, mounting evidence has unveiled the risk of aerosol transmission of the virus. Whereas caution has been taken to avoid this risk in association with clinical facilities, facilities such as spa pools and Jacuzzis, which are characterized by bubble-aerosol generation, high bather loads, and limited turnover rates, may promote aerosol transmission. Focusing on these non-clinical facilities in the built environment, a review study was undertaken. First, the typical water disinfection and ventilation-aided operations for the facilities were illustrated. Second, cross comparisons were made between the applicable standards and guidelines of the World Health Organization and countries including Australia, Canada, China, the United Kingdom, and the United States. The similarities and differences in their water quality specifications, ventilation requirements, and air quality enhancement measures were identified; there were no specific regulations for preventing aerosol transmission at those aerosol-generating facilities. Third, a qualitative review of research publications revealed the emergence of studies on potential air-borne transmission of COVID-19, but research on built facilities posing high risks of aerosol transmission remains scant. This study’s results inform key directions for future research on abating aerosol transmission of COVID-19: the development of bespoke personal protective equipment and engineering and management controls on water quality, ventilation, and air quality.